2021
DOI: 10.3390/cancers13143428
|View full text |Cite
|
Sign up to set email alerts
|

Store-Operated Calcium Channels Control Proliferation and Self-Renewal of Cancer Stem Cells from Glioblastoma

Abstract: Glioblastoma is the most frequent and deadly form of primary brain tumors. Despite multimodal treatment, more than 90% of patients experience tumor recurrence. Glioblastoma contains a small population of cells, called glioblastoma stem cells (GSC) that are highly resistant to treatment and endowed with the ability to regenerate the tumor, which accounts for tumor recurrence. Transcriptomic studies disclosed an enrichment of calcium (Ca2+) signaling transcripts in GSC. In non-excitable cells, store-operated cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…These observations suggest that combinatorial treatment of CPI444 with vatalanib with the aid of GO-PEG is effective in reducing the cellular calcium pool of GBM U87 cells. This is a very promising observation as Ca 2+ levels play a critical role not only in GSC proliferation and in glial cell function that helps in the survival and fate determination process ( 44 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggest that combinatorial treatment of CPI444 with vatalanib with the aid of GO-PEG is effective in reducing the cellular calcium pool of GBM U87 cells. This is a very promising observation as Ca 2+ levels play a critical role not only in GSC proliferation and in glial cell function that helps in the survival and fate determination process ( 44 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is a type of high-grade primary brain cancer that comprises a subpopulation called glioblastoma stem cells (GSC), which are responsible for tumor initiation, development, and recurrence following treatment ( 3 ). Calcium (Ca 2+ ) is a secondary messenger that plays a vital role in cell proliferation, cell death, differentiation, migration, metabolism, neural plasticity, and gene transcription, among other processes ( 43 , 44 ). Calcium signaling is reported to have a significant impact on neuronal cell development and function ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research showed that major modifications appear in the regulation of the SOC mechanism in glioblastoma and glioblastoma stem cells, compared to normal brain tissues ( Robil et al, 2015 ). Moreover, SOC inhibitors diminished proliferation and substantially reduces the self-renewal capacities of glioblastoma stem cells ( Terrié et al, 2021 ). However, our 18 calcium-related genes did not involve in the SOCs or ROCs.…”
Section: Discussionmentioning
confidence: 99%
“…Early evidence showed that TRPC1 presented in glioblastoma stem cells (GSC) with store-operated channel proteins of Orai1 and STIM1 [ 56 ].…”
Section: Trps In Cancer Stem Cells (Cscs)mentioning
confidence: 99%
“…Studies have identified that TRPCs can interact with STIM1 and Orai1 components to constitute store-operated Ca 2+ entry. Regarding the complex of TRPC1 with STIM1 and Orai1 in NSCs, NPCs and GSCs may contribute to store-dependent Ca 2+ signaling [ 20 , 56 , 66 ].…”
Section: Trp Roles In Stem Cellsmentioning
confidence: 99%